Developing comic text/s : representations and presentations of Jewish cultural identity through the integration of stand-up and domestic comedy - Kowen, Jacqueline Therese (Department of Drama, 2017)
This written explication deals with the integration of the forms of stand-up comedy and domestic comedy in order to create a comic text. The comic text explores issues regarding the presentation and representation of Jewish cultural identity. The integration results in both the experienced and imagined truths of the playwright to become present on stage. These were points of enquiry in the writing, directing and performing of DRIVEN: A COMEDY IN 70 MINUTES, which opened at The Intimate Theatre, Orange Street, Cape Town on the 23 November 2004. The Introduction deals with defining key terms and forms to be used and discussed in the thesis, informing the reader of the writer's purpose in creating comic text by integrating stand-up and domestic comedy. In the first chapter the generating of comic text is explored. The generating of comic text is achieved by using the comic persona. The comic persona is developed using identity, outside voice. Once the comic persona is in place it is possible to: create an authentic stage persona for the stand-up comedian and to create a 'theatrical climate' consisting of plot, characters, themes and narrative storylines. In the second chapter the idea of pastiche (borrowed elements) is explored in terms of its impact structurally and stylistically in the writing, directing and performing of DRIVEN. Structurally this impact is evident via the use of 'pastiching' the structure of situation comedy (sitcom) and stylistically through the use of Yiddish and the influence of other comedians' performance styles on the comic persona. The third chapter delves into the way Jewish cultural identity is represented through stand-up comedy and Jewish cultural identity is presented through domestic comedy. The stand-up comedian, through persona, audience relationship and other devices associated with the form, becomes the representation of Jewish cultural identity. Characters, story and situation, through the use of both comic traits (elements associated with Jewish cultural identity) and stereotypes, become the presentation of Jewish cultural identity.